Exploring Experienced EFL Teachers’ Beliefs about Speaking Tasks to Foster Speaking Skills for Senior High School Students - Adelia Vananda (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Speaking is a crucial skill that students need to master. However, many students still struggle with low proficiency in speaking. The classroom is an ideal setting for improving communication skills, namely effective speaking (Rao, 2019). To foster students’ speaking skills, structured tasks should be applied in the classroom (Akhter et al., 2020). As facilitators, the teachers need to design communicative tasks that encourage students to speak up. Furthermore, the implementation of speaking tasks should be based on teachers’ beliefs because they affect the effectiveness of education and learning opportunities (Kim, 2021). Therefore, this research aims to explore the experienced EFL teachers’ beliefs about speaking tasks to foster speaking skills for senior high school students. This study employed a case study design. The research was conducted at a public senior high school in East Java, Indonesia. The school was selected due to its A accreditation and its implementation of the Kurikulum Merdeka, which emphasizes the development of students’ speaking skills in English. I also obtained approval from the principal and English teachers to conduct research in this school. Then, the participants consisted of two experienced English teachers who met the required criteria. The data were collected through interviews and observations. During the interviews, I gathered specific data from the participants related to the teachers’ beliefs about speaking tasks to foster speaking skills for senior high school students. After that, I observed how the teachers implemented speaking tasks in the classroom that matched their beliefs to foster students’ speaking skills. Based on data obtained, this research identified six themes related to EFL teachers’ beliefs about speaking tasks to foster students’ speaking skills. These themes include beliefs about speaking tasks that: (1) invite students’ participation, (2) consider the importance of teaching speaking skills, (3) create communicative situations, (4) provide performance-based classrooms, (5) provide authentic tasks,
Reaploud Repository February_agus
Keywords: Teacher; EFL; Speak; Speaking Skills